Dimensions of Critical Reasoning in the Novel Orang-Orang Proyek by Ahmad Tohari as Alternative Teaching Materials for Literature Appreciation Learning in Junior High School: Dimensi Bernalar Kritis dalam Novel Orang-Orang Proyek Karya Ahmad Tohari sebagai Alternatif Bahan Ajar Pembelajaran Apresiasi Sastra di SMP - Muzhafar Thoriq Zainulhaq; Zuliyanti (Anthology: Journal of Language, Literature, and Learning, 2025)
The critical reasoning dimension in a novel can be one of the media in shaping students’ character education through learning. The purpose of the research is to describe the critical reasoning dimensions in the novel Orang-orang Proyek by Ahmad Tohari as an alternative teaching material for learning literary appreciation in Junior High School. This research used descriptive qualitative research method. The data collection techniques used were documentation and note-taking techniques. Data analysis techiniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of this study showed the existence of critical reasoning dimensions with elements of obtaining and processing information and ideas; analyzing and evaluating their own thinking; reflecting and evaluating their own thinking in the novel Orang-Orang Proyek by Ahmad Tohari. The novel Orang-Orang Proyek can be used as an alternative teaching material for the learning literary appreciation in Junior High School because it is in accordance with aspects of language, psychology, and cultural background. Based on the research results, the novel Orang-Orang Proyek by Ahmad Tohari can be used as an alternative teaching material for learning literary appreciation in Junior High School.   Dimensi bernalar kritis dalam sebuah novel dapat menjadi salah satu media dalam membentuk pendidikan karakter peserta didik melalui pembelajaran. Tujuan dari penelitian adalah untuk mendeskripsikan dimensi bernalar kritis dalam novel Orang-Orang Proyek karya Ahmad Tohari sebagai alternatif bahan ajar pembelajaran apresiasi sastra di SMP. Penelitian ini digunakan metode penelitian deskriptif kualitatif. Teknik pengumpulan data yang digunakan adalah teknik dokumentasi dan simak catat. Teknik analisis data yang digunakan adalah pengumpulan data, reduksi data, penyajian data, dan penarikan data. Hasil penelitian ini ditunjukan adanya dimensi bernalar kritis dengan elemen memperoleh dan memproses informasi serta gagasan; menganalisis dan mengevaluasi pemikirannya sendiri; dan merefleksi serta mengevaluasi pemikirannya sendiri pada novel Orang-Orang Proyek karya Ahmad Tohari. Novel Orang-Orang Proyek dapat dijadikan sebagai alternatif bahan ajar pembelajaran apresiasi sastra di SMP karena sesuai dengan aspek bahasa, psikologi, dan latar belakang budaya. Berdasarkan hasil penelitian, novel Orang-Orang Proyek karya Ahmad Tohari dapat dijadikan alternatif bahan ajar pembelajaran apresiasi sastra di SMP.